Study of epidemiological aspects and hormone receptor status of meningiomas - Butta, Shristi; Gupta, Manoj Kumar (International Journal of Research in Medical Sciences, 2020)
Background: Meningiomas account for about a third of all central nervous system tumours worldwide. Though very common, quite less is known about its epidemiology. This study aims to establish the epidemiological parameters and hormone receptor status (Progesterone Receptor-PR) involved in the development of Meningiomas. Methods: This observational study included 50 patients. Epidemiological parameters studied included age, sex, symptoms, history of hormone intake, smoking, recurrence, family history, history of other hormone related tumours and radiological assessment of tumour site. Surgical samples were grossed and typed according to the WHO standards. Immunohistochemical staining was done using PR to establish the role of hormonal receptors in the development of meningiomas. Results: The mean age was 46.84±13.54 years. The ratio of male and female (Male:Female) was 1.0:2.3. 48.5% of females had history of hormonal pill intake and 28.6% had hormone related tumours, of which fibroid was most common. Amongst the sites involved cerebral convexity was most common (56%). Chi-square (χ2) test showed that there was a significant association between histological grade and PR expression of the patients (p=0.0002). Conclusions: Positivity for hormone receptors like PR, increased intake of hormonal pills by females and association of meningioma with hormone related tumours indicates that hormonal milieu plays a significant role in the growth of meningiomasχχ. This could thus provide an insight to the pathogenesis of meningiomas. In addition, mifepristone, an anti-progestin could be a player in the medical management of meningiomas.